Mechanism of Secondary Glaucoma Development in HTLV-1 Uveitis - Zong, Yuan; Kamoi, Koju; Ando, Naoko; Kurozumi-Karube, Hisako; Ohno-Matsui, Kyoko (Frontiers in Microbiology, 2022)
Human T-cell lymphotropic virus type 1 (HTLV-1) was the first retrovirus identified as the causative agent of human diseases such as adult T-cell leukemia, HTLV-1–associated myelopathy, and HTLV-1 uveitis (HU). HU is one of the most frequent ocular inflammatory diseases in endemic areas, which has raised considerable public health concerns. Approximately 30% of HU patients develop secondary glaucoma, which is higher than the general uveitis incidence. We therefore investigated the mechanism underlying the high incidence of glaucoma secondary to HU in vitro. After contact with HTLV-1–producing T cells (MT-2), human trabecular meshwork cells (HTMCs) were infected. The infected cells increased in number, and nuclear factor (NF)-κB expression was activated. Contact between MT-2 cells and HTMCs resulted in significantly upregulated production of inflammatory cytokines such as IL-6 and chemokines such as CXCL10, CCL2, and CXCL-8. These findings indicate that the mechanism underlying secondary glaucoma in HU may involve proliferation of trabecular meshwork tissue after contact with HTLV-1–infected cells, resulting in decreased aqueous humor outflow. Upregulated production of inflammatory cytokines and chemokines simultaneously disrupts the normal trabecular meshwork function. This mechanism presumably leads to increased intraocular pressure, eventually resulting in secondary glaucoma.